Comparing apples to oranges? Minimizing typological biases to better classify healthcare systems globally - Lorraine Frisina Doetter; Achim Schmid; Gabriela de Carvalho; Heinz Rothgang (Health Policy Open, 2021)
The present study explores the role of typologies as an analytical device in understanding both the theoretical and empirical manifestations of healthcare systems globally. In a first step, we explore the relative benefits and limits of different classificatory logics – inductive vs. deductive – before conducting a review of scholarship on healthcare system classifications. We argue that, in order to capture the role of global actors (international organizations, donor countries etc.) in low-to-upper-middle income economies, classificatory systems must account for potential territorial shifts across the dimensions of financing, service provision and regulation defining all healthcare systems. In its absence, comparative research involving countries of significantly different levels of economic development becomes obfuscated. In an effort to redress this gap in the literature, we lay out how state, societal, market and global actors feature across different dimensions of healthcare systems, putting forth a deductively derived and actor-centered typology.